Those Who Understand It will not be Persuaded: A Performance Information Paradox. Issue 1 (2nd January 2020) - Baekgaard, Martin; Serritzlew, Søren
ABSTRACT: Performance information has been suggested as a means to inform citizens about—and shape their reactions to—public sector performance. However, individuals' ability to process information varies considerably. This implies that the same item of performance information may be understood differently by different citizens. Drawing on cognitive psychology research, we argue that cognitive differences affect citizens' ability to interpret performance information and moderate the extent to which performance information affects citizen satisfaction with public services. The argument is tested in a large-scale survey experiment. Our findings provide evidence of a performance information paradox: Those who are better able to interpret performance information do not adjust their satisfaction levels in response to the information. Conversely, those with lesser abilities to interpret and understand performance information are more responsive to it, but their responses are often based on invalid interpretations.